Crystallizing the 6S and 8S spliceosomal assembly intermediates: a complex project. (1st October 2015) - Pelz, Jann‐Patrick; Schindelin, Hermann; van Pee, Katharina; Kuper, Jochen; Kisker, Caroline; Diederichs, Kay; Fischer, Utz; Grimm, Clemens
<x xml:space="preserve">Abstract</x> The small nuclear ribonucleoproteins (snRNPs) U1, U2, U4/6 and U5 are major constituents of the pre‐mRNA processing spliceosome. They contain a common RNP core that is formed by the ordered binding of Sm proteins onto the single‐stranded Sm site of the snRNA. Although spontaneous in vitro, assembly of the Sm core requires assistance from the PRMT5 and SMN complexes in vivo. To gain insight into the key steps of the assembly process, the crystal structures of two assembly intermediates of U snRNPs termed the 6S and 8S complexes have recently been reported. These multimeric protein complexes could only be crystallized after the application of various rescue strategies. The developed strategy leading to the crystallization and solution of the 8S crystal structure was subsequently used to guide a combination of rational crystal‐contact optimization with surface‐entropy reduction of crystals of the related 6S complex. Conversely, the resulting high‐resolution 6S crystal structure was used during the restrained refinement of the 8S crystal structure.